2012
DOI: 10.1155/2012/164152
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms Dilong: Ancient, Inexpensive, Noncontroversial Models May Help Clarify Approaches to Integrated Medicine Emphasizing Neuroimmune Systems

Abstract: Earthworms have provided ancient cultures with food and sources of medicinal cures. Ayurveda, traditional Chinese medicine (TCM), and practices in Japan, Vietnam, and Korea have focused first on earthworms as sources of food. Gradually fostering an approach to potential beneficial healing properties, there are renewed efforts through bioprospecting and evidence-based research to understand by means of rigorous investigations the mechanisms of action whether earthworms are used as food and/or as sources of pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 46 publications
1
52
0
1
Order By: Relevance
“…Earthworm is one of the most widely used material medica of animal origin in traditional medicinal systems [25]. According to studies from all over the world, earthworms have been reported to serve as galactagogues and treat several aliments including hypertension, smallpox, dental problems, headache, otitis, fever, asthma, hemorrhoids, arthritis, chronic cough, jaundice, hair loss, urinary impairments, wound healing, ulcers, influenza, and other symptoms and clinical presentations [26][27][28]. Some examples are listed below in this review.…”
Section: Traditional Medicinementioning
confidence: 99%
“…Earthworm is one of the most widely used material medica of animal origin in traditional medicinal systems [25]. According to studies from all over the world, earthworms have been reported to serve as galactagogues and treat several aliments including hypertension, smallpox, dental problems, headache, otitis, fever, asthma, hemorrhoids, arthritis, chronic cough, jaundice, hair loss, urinary impairments, wound healing, ulcers, influenza, and other symptoms and clinical presentations [26][27][28]. Some examples are listed below in this review.…”
Section: Traditional Medicinementioning
confidence: 99%
“…After 30 min incubation, the absorbance (OD) of the culture plate was read at a wavelength of 572 nm on an ELISA reader, Anthos 2020 spectrophotometer. Assay was carried out in triplicate using all the chemicals and consumables with molecular biology grade in absolute sterile conditions [10] .…”
Section: Determination Of Antitumor Activitymentioning
confidence: 99%
“…This was a breakthrough in earthworm based medicine and concurrently various species of earthworms are explored for isolation of earthworm fibrinolytic enzyme (EFE) by different researchers. Further, with molecular mechanisms and physiochemical properties evaluated, it has been found that EFE has tremendous potential to dissolve thrombus in circulatory pipelines with minimal complications [10] . Recent studies have confirmed clinical significance of EFE in cerebral ischemia and more emphasis is given to refine earthworm serine protease as external fibrinolytic agent, efficiently working in neuronal tissues [9] .…”
Section: Introductionmentioning
confidence: 99%
“…This folk medicine provides a cheap method in economically challenged world (Pechter and Sherman 1983;Cooper et al 2012). The research on maggots, helminthes, and insect therapy is highly successful promising aspects in biomedicine (Bonn 2000;Amendt et al 2011).…”
Section: Introductionmentioning
confidence: 99%